Rhetorical speculations: the future of rhetoric, writing, and technology - Scott, Sundvall, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Allows scholars to explore modes of critical speculation into the transformative effect of emerging technologies, to speculate future shifts in intellectual, pedagogical, and institutional frameworks. The project repositions scholars as proprietors of our technological future rather than as secondary receivers, critics, and adjusters of the technological present.--Provided by publisher.
Unity and difference / Kristie S. Fleckenstein and Anna M. Worm -- Speculative zoopoetics / Sean Morey -- Composing with deliberate speed / Alexander Reid -- Abductive speculation / Kyle Jensen -- Gendered technologies of the self/ ie, or why we really need to "keep up" with the Kardashians / Kristine L. Blair -- Networked food narratives / Jeff Rice -- The OOOculus rift and the canon of style / Steve Holmes -- Speculative phreaking / Geoffrey V. Carter -- From Aristotle to computational topoi / Alesander Monea -- Beyond the graphic interface / Halcyon M. Lawrence -- What's funny?: looking forward while fighting back with post-conflict laughter / Sarah J. Arroyo and Bahareh B. Alaei -- Konsult / Gregory L. Ulmer.
Keywords: Rhetoric -- Study and teaching; Education -- Effect of technological innovations on; Rhetoric -- Philosophy; Future, The; Digital media; Social media in education; Communication and technology